(untitled) - Hearn, Lafcadio (Rutland, 1971)
The third book of Lafcadio Hearn's Japanese period, Gleanings in Buddha-Fields is a volume of philosophical essays and sketches inspired by the teachings of Buddha. Through a series of loosely connected essays, the author offers readers a wealth of insights into Japanese life, art and religion. When the book was first published in 1897, it attracted the attention of The New York Times: "It is only Mr. Hearn who has made us understand something of the Japanese way of looking at life and things, something of that religion which is the very soul and substance of Japanese existence, thought, and action." Today's readers are sure to recognize the elegance and depth of thought which have made the work a classic
Keywords: Buddhism,Japan; Description and travel